(untitled) (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2023)
This study aims to analyze the characteristics of cryptocurrency based on three perspectives: “economic, legal and sharia”. To answer this goal, our research utilizes a qualitative approach with a type of literature review research. Data was collected from secondary sources in the form of literature with literature analysis following the steps; material collection, descriptive, discussion, and material evaluation. From an economic perspective, cryptocurrency can be called a currency, because it fulfills the function of currency, but has not fully fulfilled the current successful currency, due to the problem of high price volatility. From a legal perspective, cryptocurrency does not meet the criteria as a currency, because currency refers to units of account and medium of exchange issued and exclusively dominated by monetary authorities and related to sovereign power where the value and credibility of a country’s currency is determined. From a sharia perspective, cryptocurrency can be considered as a property (Maal), because of desire and storage. However, it cannot be considered as a currency in sharia, because it does not fulfill a monetary value (Thamaniyyah), such as fulfilling a stand-alone value standard function and therefore still requires a fiat currency value to determine the value of cryptocurrency, but as a function of the unit of account cryptocurrency fulfills this function